1981
DOI: 10.1021/jm00144a034
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and .beta.-lactamase inhibitory properties of 2.beta.-(chloromethyl)-2.alpha.-methylpenam-3.alpha.-carboxylic acid 1,1-dioxide

Abstract: Potassium 2 beta-(chloromethyl)-2 alpha-methylpenam-3 alpha-carboxylate 1,1-dioxide (BL-P2013) and its pivaloyloxymethyl ester were prepared by the conversion of 6-aminopenicillanic acid to p-nitrobenzyl 6 alpha-bromo-2,2-dimethylpenam-3 alpha-carboxylate 1-oxide, which was rearranged with benzoyl chloride and quinoline to p-nitrobenzyl 6 alpha-bromo-2 beta-(chloromethyl)-2 alpha-methylpenam-3 alpha-carboxylate in 65% yield. Oxidation and catalytic hydrogenation afforded BL-P2013, which was found to be a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The reaction of para-substituted imines 8 with homophthalic anhydride (5) was performed in three different solvents, and the influence of the substituents on the ratios of isomers trans-9 and cis-9 formed was estimated by ' Figure 1. Hammett plots of the data listed in Table II.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reaction of para-substituted imines 8 with homophthalic anhydride (5) was performed in three different solvents, and the influence of the substituents on the ratios of isomers trans-9 and cis-9 formed was estimated by ' Figure 1. Hammett plots of the data listed in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…good as can be expected given the limitations of NMR integrations, which are only accurate within a few percent, and the values of the Hammett + constants, which are themselves subject to experimental error.10 A separate series of reactions involved competition experiments in which imine 8c was allowed to compete with imines lOa-c for reaction with homophthalic anhydride f, R=CH(CH3)2 (5) according to the general equation 5 + 8 equiv of imine 8c + 8 equiv of imines lOa-c -* products A steric effect of considerable magnitude was realized in the observation that 9c was the exclusive reaction product of all competition experiments involving imine 8c. A further result regarding electronic effects was obtained when it was found that the bulky fert-butylimine 10b reacted preferentially over the less hindered, but also less nucleophilic .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To prepare benzyl 6,6-dibromo-2-chloromethyl-2-methylpenicillanate, (1) (Gottstein et al, 1981;Zhang et al, 2006), a solution of (4) (6.1 g) in anhydrous dioxane (15 ml) was heated at reflux under nitrogen for 4 h with quinoline (1.8 g) and fresh benzoyl chloride (1.7 g). After the reaction was complete, the solvent was concentrated under reduced pressure and then diluted with excess water.…”
mentioning
confidence: 99%